1999
DOI: 10.1091/mbc.10.8.2493
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced Release of Transforming Growth Factor α Activates the Epidermal Growth Factor Receptor and Mitogen-activated Protein Kinase Pathway in Carcinoma Cells, Leading to Increased Proliferation and Protection from Radiation-induced Cell Death

Abstract: Exposure of A431 squamous and MDA-MB-231 mammary carcinoma cells to ionizing radiation has been associated with short transient increases in epidermal growth factor receptor (EGFR) tyrosine phosphorylation and activation of the mitogen-activated protein kinase (MAPK) and c-Jun NH 2 -terminal kinase (JNK) pathways. Irradiation (2 Gy) of A431 and MDA-MB-231 cells caused immediate primary activations (0 -10 min) of the EGFR and the MAPK and JNK pathways, which were surprisingly followed by later prolonged seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
232
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 301 publications
(246 citation statements)
references
References 53 publications
12
232
0
1
Order By: Relevance
“…Previous studies have shown that stimulation of the EGFR signalling pathway leads to radioresistance both in vitro and in vivo (Wollman et al, 1994;Miyaguchi et al, 1998;Akimoto et al, 1999;Dent et al, 1999). Interestingly, in the present study, we observed a strong positive association between EGFR level and radiosensitivity, which is in agreement with previous results of Bonner et al (1994Bonner et al ( , 1998Bonner et al ( , 2000.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that stimulation of the EGFR signalling pathway leads to radioresistance both in vitro and in vivo (Wollman et al, 1994;Miyaguchi et al, 1998;Akimoto et al, 1999;Dent et al, 1999). Interestingly, in the present study, we observed a strong positive association between EGFR level and radiosensitivity, which is in agreement with previous results of Bonner et al (1994Bonner et al ( , 1998Bonner et al ( , 2000.…”
Section: Discussionsupporting
confidence: 93%
“…In vitro, a 2.5-fold increased VEGF concentration has been measured in lung squamous carcinoma cells exposed to a single fraction of 15 Gy [2]. This increase was measurable up to 24 h and it was dependent on the activation of the ERK cascade through activation of the EGFR [2,9]. The activation of the ERK pathway was dose dependent with increased activity after exposure to a low radiation dose (1 Gy) [4].…”
Section: Discussionmentioning
confidence: 98%
“…VEGF is involved in development and growth of a wide variety of different tumors [15,17]. VEGF is actively secreted from tumor cells and its soluble form (VEGF 165 ) is detectable in the blood compartment [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 After phosphorylation by EGFR, cascades may transduce signals to the nucleus via downstream pathways, including the mitogen-activated protein kinase (MAPK) pathway. 6 Activation of receptor tyrosine kinases such as EGFR is recognized to have important roles in the development and progression of cancer. 7 MAPK may regulate cyclooxygenase (COX)-2 expression via both transcriptional and posttranscriptional processes.…”
mentioning
confidence: 99%